2002
DOI: 10.1016/s1535-6108(02)00044-2
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of VHL substrate binding and HIF1-α to the phenotype of VHL loss in renal cell carcinoma

Abstract: Clear-cell renal carcinoma is associated with inactivation of the von Hippel-Lindau (VHL) tumor suppressor gene. VHL is the substrate recognition subunit of an E3 ligase, known to target the alpha subunits of the HIF heterodimeric transcription factor for ubiquitin-mediated degradation under normoxic conditions. We demonstrate that competitive inhibition of the VHL substrate recognition site with a peptide derived from the oxygen degradation domain of HIF1alpha recapitulates the tumorigenic phenotype of VHL-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
286
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 419 publications
(300 citation statements)
references
References 40 publications
12
286
1
1
Order By: Relevance
“…However, recent studies have revealed that in this setting, upregulation of HIF-1a and HIF-2a activates distinct target genes and has contrasting effects on the growth of tumours (Maranchie et al, 2002;Kondo et al, 2002Kondo et al, , 2003Zimmer et al, 2004;Raval et al, 2005). These findings imply that strategies for therapeutic blockade of HIF pathways for RCC should most likely attempt to be isoform specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have revealed that in this setting, upregulation of HIF-1a and HIF-2a activates distinct target genes and has contrasting effects on the growth of tumours (Maranchie et al, 2002;Kondo et al, 2002Kondo et al, , 2003Zimmer et al, 2004;Raval et al, 2005). These findings imply that strategies for therapeutic blockade of HIF pathways for RCC should most likely attempt to be isoform specific.…”
Section: Discussionmentioning
confidence: 99%
“…They have a highly conserved domain architecture, including sites of prolyl and asparaginyl hydroxylation, and strongly promote transcription from similar hypoxia response elements (HREs). However, there is increasing evidence for the functional non-equivalence of HIF-1a and HIF-2a, and in cancer, several recent studies have indicated that, at least in certain settings, they have contrasting effects on tumour growth (Maranchie et al, 2002;Kondo et al, 2002Kondo et al, , 2003Zimmer et al, 2004;Covello et al, 2005;Raval et al, 2005). In VHL-defective renal carcinoma cells (RCC), inactivation of HIF-a proteolysis upregulates both HIF-1a and HIF-2a with global induction of HIF target gene expression (Maxwell et al, 1999), stimulating investigations of the role of the HIF pathway in tumour development (Maranchie et al, 2002;Kondo et al, 2002Kondo et al, , 2003Zimmer et al, 2004;Raval et al, 2005).…”
mentioning
confidence: 99%
“…[28][29][30] An inherited deficiency in pVHL allows HIF to become constitutively active, leading to renal cell carcinoma, further illustrating the importance of HIF in cancer pathology. 31,32 HIF is additionally hydroxylated at an asparagine residue by factor-inhibiting HIF (FIH). [33][34][35] This prevents HIF from interacting with the transcriptional coactivators p300 and CREB-binding protein (CBP), thereby reducing the transactivating activity of HIF.…”
Section: Regulation Of Hif Functionmentioning
confidence: 99%
“…[28][29][30] An inherited deficiency in pVHL allows HIF to become constitutively active, leading to renal cell carcinoma, further illustrating the importance of HIF in cancer pathology. 31,32 …”
mentioning
confidence: 99%
“…The stabilized HIF-1/2α obviously accelerates blood vessel formation around tumours, explaining the mechanism of pVHL dysfunction in tumour progression. However, more evidence shows that dysregulation of HIF-1/2α is insufficient to initiate de novo tumorigenesis in VHL-deficient cells [42][43][44][45], suggesting that pVHL may have HIF-independent functions accounting for its tumour suppression. Rb was the first tumour suppressor gene identified which negatively regulates cell proliferation [32].…”
Section: Discussionmentioning
confidence: 99%